Detection of Renal Stones by Ultrasonography - Asif Nishat, Um-e-Kalsoom; Ali, Abid; Irram, Saadia; Mazhar, Mehlab; Maqsood, Mahnoor; Muzafar, Saba; Ashraf, Nadia; Noor, Ayesha (Medical Science Journal for Advance Research, 2023)
Background: Kidney stones also known as renal stones are hard deposits made of minerals that develop in the urinary system or kidneys. Numerous symptoms, including excruciating pain in the lower back, abdomen, or groin, nausea, and vomiting, can be brought on by renal stone. Objective: To evaluate the accuracy of ultrasonography for the presence, location, and site of stones in patients with acute renal colic Methods: This research was conducted in the radiology department of the Jalal Pur Diagnostic Centre. Data were acquired from October 2022 to March 2023.100 patients were included in the study. Patient-informed permission was acquired following the ethical standards outlined by the research committee. Results. The study shows that 74% of patients have unilateral renal stones while 26% have bilateral renal stones. About 43 people had urolithiasis on the left side. The majority of stones were present in the lower pole of the kidney. Conclusion: Ultrasonography can be utilized as a primary evaluation technique in patients presenting with acute renal colic. Males are most commonly affected by renal stones than females and patients between the ages of 31 and 45 are the most usually affected.